2016
DOI: 10.1038/nphys3739
|View full text |Cite
|
Sign up to set email alerts
|

Collective stochastic coherence in recurrent neuronal networks

Abstract: Recurrent networks of dynamic elements frequently exhibit emergent collective oscillations, which can display substantial regularity even when the individual elements are considerably noisy. How noise-induced dynamics at the local level coexists with regular oscillations at the global level is still unclear. Here we show that a combination of stochastic recurrence-based initiation with deterministic refractoriness in an excitable network can reconcile these two features, leading to maximum collective coherence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 54 publications
(93 reference statements)
3
41
0
Order By: Relevance
“…These results suggest that during the first part of the transition from deep to light levels of anesthesia (from D1 to D2) the SO not only became faster but also more regular, since the interquartile range, representing the range of the frequencies visited around this median value, was reduced. This increased regularity of SO is highly suggestive that there is an optimal level of the network excitability to express this rhythm, as it has been reported for the cortex in vitro (Sancristóbal et al, 2016). We explore this quantitatively in our computer model (see below).…”
Section: Gradual and Abrupt Changes In The Oscillatory Patterns When supporting
confidence: 61%
See 1 more Smart Citation
“…These results suggest that during the first part of the transition from deep to light levels of anesthesia (from D1 to D2) the SO not only became faster but also more regular, since the interquartile range, representing the range of the frequencies visited around this median value, was reduced. This increased regularity of SO is highly suggestive that there is an optimal level of the network excitability to express this rhythm, as it has been reported for the cortex in vitro (Sancristóbal et al, 2016). We explore this quantitatively in our computer model (see below).…”
Section: Gradual and Abrupt Changes In The Oscillatory Patterns When supporting
confidence: 61%
“…We observed that while the Up state duration remained almost constant with a small tendency to increase, the Down state duration decreased monotonically, at some point converging to duration values very similar to those of the Up state, resulting into an increase in frequency and regularity of the SO ( Figure 2C). Remarkably, a similar stability of the Up state duration and the changes of the Down state duration has been also found in vitro when the network excitability is modulated both by extracellular potassium concentration (Sancristóbal et al, 2016) and by applying exogenous electric fields (D'Andola et al, 2018) suggesting that regular SO is an attractive dynamical regime for the isolated cortex (Sanchez -Vives et al, 2017).…”
Section: Appearance Of a New Activated Statementioning
confidence: 61%
“…While in many cases coupling merely coordinates dynamical regimes that are already present in the isolated elements, in others it underlies the emergence of novel behaviors that would not exist in the absence of interaction between the elements [4,5]. In the brain, examples of such emergent behavior exist at the microscopic scale of networks of neurons, in the form of, for instance, collective oscillations arising from a balance between excitation and inhibition [6,7] and recurrent up/down dynamics [8]. Much less is known, however, about the emergent behavior of the brain at the mesoscopic level of coupled brain areas.…”
Section: Introductionmentioning
confidence: 99%
“…-Since the pioneering work of Donald Hebb [1], seven decades ago, the common hypothesis in the dynamics of neural networks [2][3][4][5][6] is that the network links, the synapses, are the building blocks of our brain which are responsible for the learning process [7,8]. The basic idea proposed by Hebb was that neurons that fire together, wire together, indicating a local dynamical learning rule to imprint changes in the strengths of the synapses.…”
mentioning
confidence: 99%